Woven Fabric Carbon Fibre Composites Hybrid Joints under Quasi-Static Testing - Lee, S.Y.; Ahmad, H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Twill weave carbon fibre reinforced polymer (CFRP) hybrid adhesively bonded-bolted joints was investigated on bearing stress at failure in experimental programmes. The present paper comprises effects of joint type, normalised coupon width (W/d), laminate orientations and bolt load as specified in designed series. All CFRP hybrid joints exhibited cohesive failure before ultimate failure i.e., net-tension and bearing/net-tension failures. Bearing stress at failure was found to increase with normalized W/d and small W/d led to net-tension failure occurrence. Double-lap joints (DLJs) were stronger than single-lap joints (SLJs) due to secondary bending phenomenon in SLJs. Cross-ply presented greater strength than quasi-isotropic lay-up caused by the presence of 0˚ fibres orientation. Clamped condition (applied torque, T = 5 Nm) may change the critical W/d than finger-tight (FT) case as net-tension failures is likely to occur under clamped condition.